Hubungan D-dimer dengan tingkat keparahan infeksi COVID-19 - Kadek Anggiswari Pradnya Angela; I Made Duwi Sumohadi (Intisari Sains Medis, 2022)
Introduction:  Inflammation response and endothelial damage caused by COVID-19 resulting coagulopathy by increased D-dimer level. High D-dimer can predict COVID-19 severity. This research conducted to know the correlation, risk, and prediction of severe COVID-19 infection in patients with high D-dimer levels. Method: Cross-sectional with bivariate and multivariates logistic regression analysis was conducted. Samples are ≥18 years old with COVID-19 hospitalized in Tabanan regional hospital during October 2021- March 2022. Data collected from medical records. Patients with chronic liver disease, congestive heart disease, malignancy, post-surgery, pregnancy, and deep vein thrombosis are excluded. COVID-19 severity criterias are based on COVID-19 management protocol. Result: Of 84 patients, 63.1% males and 58.3% ≥ 60 years old. Mean D-dimer level in severe COVID-19 patients are 3,256.06 ng/ml, and 1,543.02 ng/ml in non-severe (p = 0.014, CI 95%: 435.568–2,990.51). Cut-off point of D-dimer level is 788.5 ng/ml, with 71.9% sensitivity and 69.2% specificity on the receiver operating characteristics curve. A significant correlation is found between D-dimer level above cut-off and COVID-19 infection severity (OR 5.75, CI 95%: 2.18-15.16, p= 0.001). Correlation is still significant after variables age ≥60 years old and DM comorbidity adjusted (OR 5.32, CI 95%: 1,922-14,729, p=0.001). Probability of severe COVID-19 infection in patients ≥60 years old with D-dimer level > 788.5 ng/ml and has DM comorbidity is 83.24%. Conclusion: COVID-19 infection severity correlates with increased D-dimer levels with risk more than 5 times after variables age ≥60 years old and DM comorbidity adjusted, with moderate categorized prediction accuracy.   Pendahuluan: Respon inflamasi dan kerusakan endotel akibat COVID-19 menyebabkan terjadinya koagulopati, ditandai dengan peningkatan kadar D-dimer. D-dimer tinggi diperkirakan dapat memprediksi keparahan COVID-19. Penelitian ini dilakukan untuk mengetahui hubungan, besar risiko, dan prediksi terjadinya infeksi COVID-19 berat pada penderita D-dimer tinggi. Metode Penelitian:  Penelitian ini merupakan penelitian cross-sectional dengan analisis bivariat chi-square dan regresi logistik multivariat. Sampel adalah penderita ≥18 tahun dengan COVID-19 yang dirawat di RSUD Tabanan periode Oktober 2021-Maret 2022. Data diambil dari rekam medik. Penderita penyakit hati kronik, penyakit jantung kongestif, keganasan, paska pembedahan, hamil, dan deep vein thrombosis dieksklusi. Kriteria keparahan COVID-19 menggunakan buku pedoman protokol tatalaksana COVID-19. Hasil Penelitian: Dari 84 penderita memenuhi kriteria, 63,1% laki-laki, 58,3% umur ≥ 60 tahun. Rata-rata kadar D-dimer pada infeksi COVID-19 berat 3.256,06 ng/ml dan 1.543,02 ng/ml pada infeksi COVID-19 tidak berat (p = 0,014, IK 95 %: 435,568 – 2.990,51).  Nilai cut off kadar D-dimer didapatkan 788,5 ng/ml dengan sensitivitas 71,9%, spesifisitas 69,2% pada receiver operating characteristics curve. Didapatkan hubungan bermakna D-dimer diatas cut off dengan tingkat keparahan infeksi COVID-19 (OR 5,75, IK 95%: 2,18-15,16, p= 0,001) Hubungan ini tetap bermakna setelah diperhitungkan faktor usia ≥60 tahun dan komorbid DM (OR 5,32, IK 95%: 1.922-14.729, p = 0,001). Probabilitas terjadinya infeksi COVID-19 berat pada penderita usia ≥60 tahun dengan D-dimer > 788,5 ng/ml dan komorbid DM adalah 83,24%. Simpulan: Keparahan infeksi COVID-19 berhubungan dengan peningkatan kadar D-dimer dengan risiko lebih dari lima kali setelah diperhitungkan faktor usia dan komorbid DM dengan akurasi prediksi kategori sedang.